(untitled) (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
This teaching-methodical manual is written for teachers within the special education system and general education schools with inclusive education programs, focusing on the educational challenges faced by deaf and hard-of-hearing children. It offers an in-depth description of Uzbek sign language and the structured system for its instruction.